Social Capital in Coastal Community Development: A Bibliometric Analysis - Suprianto Suprianto; Rahmat J Rahmat J; Muh. Ersyad Indra Praja; Yusran Yusran; Tri Nurfadilla; Ananda Febrina Awalia (Jurnal Riset Diwa Bahari (JRDB), 2024)
Social capital has become an essential foundation for strengthening sustainable coastal community development by fostering collective action, trust, social networks, and collaborative governance. As coastal communities increasingly confront environmental degradation, climate change, resource depletion, and socioeconomic vulnerability, research on the role of social capital has expanded significantly across multiple disciplines. However, the intellectual landscape and thematic evolution of this research remain insufficiently synthesized. This study aims to analyze global research trends on social capital in coastal community development through a bibliometric analysis of publications indexed in the Scopus database from 2016 to 2023. A comprehensive search strategy was employed to retrieve relevant publications, which were subsequently analyzed using descriptive bibliometric techniques. Publication trends, leading journals, authors, countries, institutions, and subject areas were examined to characterize the development of the field. Furthermore, VOSviewer was utilized to visualize keyword co-occurrence, co-authorship networks, and thematic clusters, providing insights into the intellectual structure and emerging research directions. The results indicate a consistent increase in scientific publications during the study period, reflecting growing scholarly interest in the contribution of social capital to participatory governance, community empowerment, sustainable livelihoods, coastal resource management, and disaster resilience. Recent studies have increasingly incorporated themes related to climate adaptation, blue economy, ecosystem-based management, and social resilience, demonstrating the interdisciplinary expansion of the field. Nevertheless, important research gaps remain concerning comparative cross-regional analyses, the measurement of social capital in coastal settings, and its long-term influence on sustainable development outcomes. This bibliometric analysis provides a comprehensive overview of the evolution of research on social capital in coastal community development and identifies promising directions for future studies to support evidence-based policies and sustainable coastal governance.